Addressing infodemic for pandemic preparedness in the digital age: a focus on Middle Africa - Penka, Marthe Bogne; Tangang, Andrew; Alang Wung, Ernest; Tata Kelese, Mark; Okwen, Patrick (Frontiers in Public Health, 2024)
Background The 21 century reveals itself with a damaging information crisis, challenging and undermining efforts made to increase the uptake of scientific research evidence in both policy and practice. WHO recognizes misinformation and disinformation as one of the drivers of pandemic spread and impact and has dedicated a policy brief for pandemic preparedness to this. We examine the impact of mis/disinformation on the use of research evidence in public policy decision making in West and Central Africa and reflect on how this can be considered in future pandemic preparedness. Objectives What factors affect uptake of scientific evidence in disease outbreak in Africa? Methods We used the JBI Scoping Review and Prevalence/Incidence Review approaches to synthesize best available evidence. We used a DELPHI survey to gather experiences of policy makers, practitioner, and citizens on mis/disinformation and its impact at stage I from Cameroon, Nigeria, and Senegal. A second stage DELPHI survey explored solutions to various problematics identified in stage I. We used MAXQDA for qualitative data analysis. Results The results of this research revealed origins (n=5), transmission platforms (n=15), cases (n=4), mitigation strategies (n=6), impacts (n=4) of infodemic on policy design, implementation, and uptake. Online platforms was identified as main source of infodemic in 53.3% cases compared to 46.7% offline platforms. We conclude that the severity of COVID-19 as a global pandemic has revealed the danger of mis/disinformation with a considerable number of reported studies from Middle Africa demonstrating significant negative impact on evidence informed policymaking. Discussions Digital technologies, especially social media plays a key role in infodemics propagation. In future pandemic preparedness, stakeholders must consider using digital tools and platforms for prevention and mitigation of pandemics. This study adds new evidence to the existing body of evidence on the need to address infodemic within the precincts of future pandemic preparedness in Middle Africa.